Real-time audio encryption and processing - Baduel, Nico Karlo
Audio encyption is a very useful technique for stopping unwanted signal interception of any transmitted audio. We developed a system that encrypts an analog audio signal in real-time using a stream cipher algorithm; then seeds it to another system that decrypts and plays the original audio signal. Our system can be really useful if implemented in real-life networks where transmission is very crucial. Our system's main advantage would be its speed; it will be designed to encrypt and transmit the data right after the audio signal is received as input. The system is developed and implemented in Android.